Dry grassland types in the Prespa National Park (NW Greece), including the southernmost occurrence of the priority habitat type “Pannonic sand steppes” (code 6260) - Fotiadis, Georgios; Vrahnakis, Michael; Kazoglou, Yannis; Tsiripidis, Ioannis (Hacquetia, 2015)
A recently completed project on the Natura 2000 sites of Prespa National Park revealed that the area hosts 49 habitat types according to the EU classification, of which eight have a narrowly restricted distribution in Greece. The priority habitat type “*6260 Pannonic sand steppes” is reported here for the first time for Greece. The new locality represents its southernmost occurrence on the Balkan Peninsula. The aim of this paper therefore is to describe the Greek stands of this habitat type, investigate the factors affecting its occurrence and discuss the associated conservation issues. This is based on a total of 87 relevés sampled for this study and 8 additional relevés from the literature. The relevés were classified by applying TWINSPAN and ordinated using Detrended Correspondence Analysis (DCA). Six vegetation units could be distinguished. One of these corresponds to the habitat type *6260 and was found exclusively on inland sand dunes. Syntaxonomically, we assigned this unit to the alliance Sileno conicae-Cerastion semidecandri s.l. of the class Koelerio-Corynephoretea. Its occurrence in the study area seems to be determined by climatic factors, as well as by the sandy substrate, while anthropogenic disturbances such as grazing also appear to be beneficial to some degree. Apart from the Koelerio-corynephoretea, another five grassland classes were distinguished in the national park, namely the Thero-Brachypodietea, Stellarietea mediae, Festuco-Brometea, Daphno-Festucetea and Juncetea trifidi.